Cities in Africa before 1900. Historiography and Research Perspectives - Clélia Coret; Roberto Zaugg; Gérard Chouin (Afriques, 2020)
What new issues arise several decades after the first academic studies? What are the answers and what sources are mobilized? This special issue proposes a historiographical review of research conducted on cities, taking into account the most recent methodological reflections on the issue of the relationship between the urban territory and the exercise of power before the 20th century, focussing on its material and symbolic aspects. Case studies in the Maghreb, West Africa’s forest and Sahelian regions and East Africa examine these stakes.